A Palavra que vivifica e salva contra o mal da palavra que mata : imprensa católica - Belém (1910-1930) - Goudinho, Liliane do Socorro Cavalcante (2015)
This work aims at understanding the Catholic press after the separation of church and State in Brazil (1889) and how the campaigns known as "Boa Imprensa" echoed specifically in Belem in the period 1910 to 1930 contributing to the strengthening of the institution and the organization of the Catholic newspapers that existed in the city. The research tries to understand the diocesan expansion and the parish reorganization filed by the Church as a way of reaction to the end of patronage and the changes in the late years of the nineteenth century (which was conventionally called "modernity").The discussions focused on the main Catholic newspaper of this period in Pará: A Palavra, which included the influence of priests and lay people, being directed by Paulino de Brito and Florence Dubois (he was a priest of the Barnabites religious order and main protagonist of polemics). This press positioned itself as an instrument of evangelization and combating the supposed enemies of the Catholic faith, facing Spiritualists and Protestants. The Catholic periodicals assumed the pedagogical mission control and moralization of customs, directing much of the articles to women; through these documents, they censored the "dangers of modernity": reading of novels, going to the cinema, movies, dances, and fashions. This research analyzes the construction process of Catholic Church‟s discourse in Belém through this press and how these documents dialogued with local circumstances, reflected negotiations in interests of the diocese, Barnabites and other historical subjects who had access to such journals, and how its representations, which sometimes were reinterpreted or appropriated, generated actions and polemics written and rewritten in the local press